Pragmatisme Politik Partai Kebangkitan Bangsa terhadap Peningkatan Jumlah Suara dalam Pemilihan Legislatif di Kota Padang 2024 - Kurnia Aznar Putra; Aldhy Darza Yustika; Doni Hendrik; Irawati Irawati (Jurnal Politik dan Pemerintahan Daerah, 2025)
The purpose of this research is to see whether the increase in PKB votes comes from the shift in party ideology to the center to get a lot of masses to the phenomenon of politicians moving parties. This research uses a qualitative approach with a type of literature study, namely in-depth data search or observation (observation) with the source of reference books and similar research results. This research shows that the increase in PKB votes to get 4 seats in the Padang City DPRD is related to the strategy of adapting to the political aspirations of the community by applying the catch all party approach, namely by shifting the ideology of the Islamic party to become an open party and absorbing more community support. In addition, the recruitment of legislative candidates who are open to anyone, including politicians from other parties who already have an electoral history, is one of the key factors in increasing PKB votes. The recruitment of politicians who already have electoral history and fame has proven to play a central role in bringing PKB into the legislative arena in Padang City.